Assessing the effects of 10 weeks of fitlight-based plyogility training on basketball players’ attention, agility, dribbling, and shooting skills - ahmad hassan (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Plyometric and agility (plyogility) training; particularly with cognitive components including light, as in FITLIGHT systems offer immense advantages to enhancing physical performance and cognitive functning.